2007
DOI: 10.1104/pp.107.096214
|View full text |Cite
|
Sign up to set email alerts
|

The Maize Zmsmu2 Gene Encodes a Putative RNA-Splicing Factor That Affects Protein Synthesis and RNA Processing during Endosperm Development

Abstract: We characterized two maize (Zea mays) mutants, zmsmu2-1 and zmsmu2-3, that result from insertion of a Mutator (Mu) transposable element in the first exon of a gene homologous to the nematode gene, smu-2, which is involved in RNA splicing. In addition to having a starchy endosperm with reduced levels of zein storage proteins, homozygous zmsmu2-1 mutants manifest a number of phenotypes, including defective meristem development. The zmsmu2 mutants have poor seedling viability and surviving plants are sterile. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The BLASTX analysis revealed the chimeric nature of the MuDRcontaining ESTs showing similarity to a predicted pre-mRNA-splicing factor 18-like (XP_004958093). It has been previously reported that MuDR insertion in the first exon of a gene encoding a splicing factor has pleiotropic effects (Chung et al 2007) caused by inefficient rRNA processing in endosperm as well as by up-regulation of ribosomal protein genes (Chung et al 2009). Upregulation of two ribosomal genes, one in the diploid genotype and the other in the tetraploid ones, was also observed in the euploid series (Cervigni et al 2008b, Selva et al 2012.…”
Section: Discussionmentioning
confidence: 94%
“…The BLASTX analysis revealed the chimeric nature of the MuDRcontaining ESTs showing similarity to a predicted pre-mRNA-splicing factor 18-like (XP_004958093). It has been previously reported that MuDR insertion in the first exon of a gene encoding a splicing factor has pleiotropic effects (Chung et al 2007) caused by inefficient rRNA processing in endosperm as well as by up-regulation of ribosomal protein genes (Chung et al 2009). Upregulation of two ribosomal genes, one in the diploid genotype and the other in the tetraploid ones, was also observed in the euploid series (Cervigni et al 2008b, Selva et al 2012.…”
Section: Discussionmentioning
confidence: 94%
“…In plants, a variety of RNA splicing factors have been shown to have specific roles in abiotic stress tolerance and flowering time (reviewed in Lorković , 2009). Mutants and misexpression transgenics of both U2 and U12 splicing factors can have pleiotropic developmental defects (Lopato et al, 1999;Kalyna et al, 2003;Ali et al, 2007;Chung et al, 2007;Coury et al, 2007;Kim et al, 2010). Most plant genes contain introns that must be removed for protein expression; therefore, RNA splicing should be an essential function for cell viability.…”
Section: Weak Alleles Of Rgh3 Reveal Developmental Roles For Maize Urpmentioning
confidence: 99%
“…For pull-down experiments where GST fusion proteins were used as a bait protein, cell lysates containing the fused target proteins with a 6XHis tag were prepared in lysis buffer (50 mM Tris, pH 8.5, 150 mM NaCl, 1 mM dithiothreitol, 1 mM EDTA, and 0.2 mM phenylmethanesulfonyl fluoride) containing 1% (v/v) Triton X-100. Purification of GST and GST-ZmSMU2 was performed as described by Chung et al (2007). Cell lysates containing 0.1 to 0.5 mg of target proteins were preincubated with 0.5 mg of GST and 50 mL of a 50% (v/v) glutathione-agarose slurry (Sigma) at 4°C for 1 h. The cleared cell lysates were added to 50 mL of a 50% (v/v) glutathioneagarose slurry and 10 mg of GST, GST-AtSMU2, or GST-ZmSMU2 protein.…”
Section: Expression Of Recombinant Proteins In Escherichia Coli and Imentioning
confidence: 99%